Analisis Pembayaran Penggajian Tambahan Penghasilan Pegawai Bagi PNS Bagian Protokol Dan Komunikasi Pimpinan Di Sekretariat Daerah Kabupaten Magelang - Rahmawan, Luki (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This research discusses the process of paying additional employee income for civil servants in the Leadership Protocol and Communication section at the Regional Secretariat of Magelang Regency. This research method uses a qualitative approach with descriptive methods, aiming to reveal events, facts, phenomena, variables and circumstances that occurred during the research, in detail and according to what actually happened. This research data is divided into two types, namely secondary data and primary data. Based on Regent's Regulation Number 49 of 2023 concerning Additional Income for State Civil Service Employees in the Magelang Regency Government, the activity of providing additional Employee Income in the Protocol and Communication Section of the Regional Secretariat Leadership is quite good. Employee performance in carrying out their duties has met the criteria (based on Regent Regulation Number 49 of 2023 in Article 4) to receive Additional Employee Income. Firstly, additional employee income is given to the State Civil Apparatus in Magelang Regency based on objective considerations and regional financial capacity in accordance with statutory provisions. The two factors that influence the reduction in additional employee income are attendance, punctuality, participation in morning assembly or ceremonies, discipline, compliance in setting employee performance targets. Keywords: Payment of Additional Employee Income, Leadership Protocol and Communication Section, Regional Secretariat, Regent Regulation Number 49 of 2023.